2015
DOI: 10.2144/000114297
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Migration of Neutrophils Through an Electrospun Nanofibrous Membrane

Abstract: The study of immune cell migration is important for understanding the immune system network, which is associated with the response to foreign cells. Neutrophils act against foreign cells before any other immune cell, and they must be able to change shape and squeeze through narrow spaces in the extracellular matrix (ECM) during migration to sites of infection. Conventional in vitro migration assays are typically performed on two-dimensional substrates that fail to reproduce the three-dimensional (3-D) nature o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
(14 reference statements)
0
5
0
Order By: Relevance
“…Technically, the PCL-NM can be easily assembled into the two-layer system, which mimics multilayers of cells in tissue. Moreover, PCL nanofibers are inert and biocompatible in immune cell culture because the adhesion of DCs to PCL nanofibers does not affect their activation status [ 12 , 13 ]. Finally, 3D migration to surrounding bacteria and phagocytosis processes in the PCL-NM can be visualized though a live cell-imaging setup.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Technically, the PCL-NM can be easily assembled into the two-layer system, which mimics multilayers of cells in tissue. Moreover, PCL nanofibers are inert and biocompatible in immune cell culture because the adhesion of DCs to PCL nanofibers does not affect their activation status [ 12 , 13 ]. Finally, 3D migration to surrounding bacteria and phagocytosis processes in the PCL-NM can be visualized though a live cell-imaging setup.…”
Section: Discussionmentioning
confidence: 99%
“…For optimal cellular infiltration, we developed a hybrid electrospun poly(ε-caprolactone) (PCL)-nanofibrous membrane (NM) (PCL-NM) consisting of nano- as well as submicron-scale fibers and we used the PCL-NM to mimic the naturally occurring crosstalk between immune and cancer cells [ 11 ]. Additionally, we demonstrated that neutrophils migrate against interleukin (IL)-8 in an electrospun PCL-NM [ 12 ]. PCL is a Food and Drug Administration (FDA)-approved biocompatible and biodegradable aliphatic polyester [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…NF was fabricated by a previously reported electrospinning method [ 20 , 21 ]. Briefly, nanofibers were produced by diluting high molecular weight (80,000 MW) polycaprolactone (Sigma-Aldrich, St. Louis, MO, USA) at a concentration of 17% in a 1:1 mixture of chloroform (99.5%, Samchun Pure Chemical Co., Ltd., Seoul, Korea) and dimethylformamide (Sigma-Aldrich).…”
Section: Methodsmentioning
confidence: 99%
“…This technique has the advantages to produce homogeneous fiber sizes. Polymers such as polycaprolactone have been used in order to study immune cells migration through a fibrous membrane of various density (Jin et al 2015 ). The 2D structures are then used as a scaffold, and can be coated with collagen for more physiological properties of basement membrane.…”
Section: Migration Of Immune Cells In Diverse Microfabricated Geometriesmentioning
confidence: 99%